Enhancing Qualitative Research: The Use of Design Probes and Cooking Sessions Deepens the Understanding of 9- to 11-Year-Old Children’s Food Perceptions - Lotte Pater; Elizabeth H. Zandstra; Vincenzo Fogliano; Bea L. P. A. Steenbekkers (International Journal of Qualitative Methods)
Qualitative research with children is critical for tailoring interventions and decisions that directly impact their well-being and future. Yet, the involvement of children in the field of sustainable food perception is still limited because of children’s unique cognitive needs. This research aims to reflect upon design probes, one-to-one interviews, and cooking sessions as complementary qualitative research methods for understanding children’s perception of plant-based food products. A three-stage study was designed to holistically address children’s competences, communication preferences, and experiences. In the first stage, children received a design probe box with assignments to be performed individually at home, aiming at gathering data about their everyday life and experiences in a familiar, informal setting. In the second stage, one-to-one interviews were conducted to reflect upon the assignments and to dive deeper into the reasons behind children’s experiences. In the final stage, children created a pizza with their classmates in groups of 3–6 children at their schools. This paper focuses on the evaluation of these different qualitative research methods for understanding children’s perceptions. Results demonstrate that utilizing a combination of methods to explore food perceptions of children aged 9 to 11 can lead to a more comprehensive and profound understanding of their viewpoint. Design probe activities and cooking sessions create feelings of empowerment amongst children as children are the creators of crafts or products. These new child-centered qualitative participatory research methods enable to perform the intervention in a natural and real-life context, favouring the expression of thoughts about the research topic. The findings provide evidence that participatory methods should be combined with traditional methods, such as one-to-one interviews, to get richer and more detailed insights into children’s food perceptions in real-world contexts.